2019
DOI: 10.3390/sports7070176
|View full text |Cite
|
Sign up to set email alerts
|

Motor Competence in Adolescents: Exploring Association with Physical Fitness

Abstract: The purpose of this study was twofold: First, to examine the correlation between adolescents’ performance on the Movement Assessment Battery for Children -2 (MABC-2) and the Test of Motor Competence (TMC), and second, to interpret the correlation between performance on physical fitness measures and motor competence. This study had a cross-sectional design, in which 101 adolescents age 15–16 years were recruited. The participants were assessed with the MABC-2 (eight tasks), the TMC (four tasks) and physical fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
1
6
0
2
Order By: Relevance
“…The findings indicated moderate correlations between total score MABC and total z-score TMC sharing 21% of the variance. This is in line with the results from Gísladóttir et al (2019) with a sample of adolescents in which the shared variance (18%) between the MABC-2 and TMC was of a similar magnitude as in the present study. The notion that there was only 21% shared variance between the MABC and TMC indicated that there was only moderate construct validity (Cronbach and Meehl, 1955).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings indicated moderate correlations between total score MABC and total z-score TMC sharing 21% of the variance. This is in line with the results from Gísladóttir et al (2019) with a sample of adolescents in which the shared variance (18%) between the MABC-2 and TMC was of a similar magnitude as in the present study. The notion that there was only 21% shared variance between the MABC and TMC indicated that there was only moderate construct validity (Cronbach and Meehl, 1955).…”
Section: Discussionsupporting
confidence: 93%
“…The TMC was designed to give an objective quantification of motor performance across the life span (Sigmundsson et al, 2016). However, the TMC results have not yet been compared with another test for motor competence in this age group only for adolescents (Gísladóttir et al, 2019).…”
Section: Motor Assessmentsmentioning
confidence: 99%
“…In other words, improvement in one motor skill does not ensure improvement in other motor skills. This hypothesis is supported by empirical studies showing low correlations between individual motor skill items in children (Haga et al, 2008;Lorås and Sigmundsson, 2012;Stöckel and Hughes, 2016;Gísladóttir et al, 2019). For example, Haga et al (2008) found mostly no or non-significantly weak correlations between items of the Movement Assessment Battery for Children in 4-year-old children.…”
Section: Introductionmentioning
confidence: 73%
“…La competencia motriz es la manifestación de la habilidad motriz que contribuye a disponer de un mayor repertorio de actos motores en los que sentirse competente y adaptarse al entorno inmediato (Rosa-Guillamón y ; incluyendo tanto la coordinación de las habilidades motoras finas (ej., Destreza manual) como gruesas (ej., Equilibrio estático y dinámico) (Gísladóttir, Haga y Sigmundsson, 2019).…”
Section: Introductionunclassified
“…Un metaanálisis reciente ha indicado una relación positiva, de moderada a elevada, entre la CA y la CM, que se fortalece con el aumento de la edad. Sin embargo, los resultados también indican que se necesita más investigación para evaluar similitudes y diferencias en los instrumentos utilizados en la primera etapa escolar (Utesch, Bardid, Büsch y Strauss, 2019), dado que otros estudios con otros instrumentos utilizados no evaluaron todas las dimensiones de la CM: locomotor, estabilidad y control de objeto (Luz, Cordovil, Almeida y Rodrigues, 2017) sugiriendo que diferentes baterías de prueba más limitadas pueden causar discrepancias en los resultados con respecto a la correlación entre la CM y la CA (Gísladóttir, Haga y Sigmundsson, 2019).…”
Section: Introductionunclassified